Zeolitic imidazolate frameworks 67 (ZIF-67) como molde para o desenvolvimento de novos eletrocatalisadores na reação de evolução de oxigênio - Lourenço, Annaíres de Almeida (2020)
Hydrogen gas (H2) has recently stood out among clean and renewable energy sources. This gas can be obtained from the electrolysis of water which consists of two semi-reactions, Hydrogen Evolution Reaction (HER) and Oxygen Evolution Reaction (OER). However, this process, especially OER, needs a high potential to occur, being necessary to use catalysts for this reaction to be viable, and cobalt-based oxides are among the most promising electrocatalysts. In this context, this work reports the synthesis of bimetallic cobaltites with Mn, Ni and Zn using Zeolitic Imidazolate-67 structures (ZIF-67) as model. The impregnation of metals in the ZIF-67 structure was evaluated in ethanol and methanol media, in order to obtain the best synthetic route. The powder X-ray diffraction patterns did not show changes in crystalline phase after the impregnation of the metals in the ZIF-67. By thermogravimetric analysis, the presence of the impregnated metals on the ZIF-67 was confirmed, with greater quantity when the synthesis was done in ethanol. Undoped (ZIF-67(C)) and doped (Co/M/C(S), with M = Mn, Ni and Zn and S = E and M) cobaltites were obtained after chemical treatment at 350°C. The XRD patterns with Rietveld refinement revealed the formation of composites of spinel structures NiO/NiCo2O4, ZnO/ZnCo2O4 and Co3O4/Mn0,8Co2,2O4 for species synthesized in ethanol and NiCo2O4, ZnO/ZnCo2O4 e Mn0,4Co2,6O4 for those from the methanol route, with the atoms of Ni, Zn and Mn located, preferably, in octahedral sites, according to the Raman spectra. The dispersive energy spectroscopy (EDS) analyses show the homogeneous distribution of atoms in compounds originated from methanol synthesis. The electrocatalytic activity in OER was investigated in an alkaline medium and bimetallic cobaltites showed better performance compared to ZIF-67(C). Co/NiC(E) has 333 mV overpotential to produce a current density of 10 mA cm-2, the best result, whileCo/Ni/C(M) is more efficient at 100 mA cm-2 (η = 436 mV).